The safety of early discharge following transfemoral transcatheter aortic valve replacement under general anesthesia - Koren, Ofir; Patel, Vivek; Kohan, Siamak; Naami, Robert; Naami, Edmund; Allison, Zev; Natanzon, Sharon Shalom; Shechter, Alon; Nagasaka, Takashi; Al Badri, Ahmed; Devanabanda, Arvind Reddy; Nakamura, Mamoo; et al. (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: There is growing evidence of the safety of same-day discharge for low-risk conscious sedated TAVR patients. However, the evidence supporting the safety of early discharge following GA-TAVR with routine transesophageal echocardiography (TEE) is limited. AIMS: To assess the safety of early discharge following transcatheter aortic valve replacement (TAVR) using General Anesthesia (GA-TAVR) and identify predictors for patient selection. METHODS: We used data from 2447 TEE-guided GA-TAVR patients performed at Cedars-Sinai between 2016-2021. Patients were categorized into three groups based on the discharge time from admission: 24h, 24-48h, and >48h. Predictors for 30-day outcomes (cumulative adverse events and death) were validated on a matched cohort of 24h vs. >24h using the bootstrap model. RESULTS: The >48h group had significantly worse baseline cardiovascular profile, higher surgical risk, low functional status, and higher procedural complications than the 24h and the 24-48h groups. The rate of 30-day outcomes was significantly lower in the 24h than the >48h but did not differ from the 24-48h (11.3 vs. 15.5 vs. 11.7%, p=.003 and p=0.71, respectively). Independent poor prognostic factors of 30-day outcomes had a high STS risk of ≥8 (OR 1.90, 95% CI 1.30-2.77, E-value=3.2, P<.001), low left ventricle ejection fraction of <30% (OR 6.0, 95% CI 3.96-9.10, E-value=11.5, P<.001), and life-threatening procedural complications (OR 2.65, 95% CI 1.20-5.89, E-value=4.7, P=0.04). Our formulated predictors showed a good discrimination ability for patient selection (AUC: 0.78, 95% CI 0.75-0.81). CONCLUSION: Discharge within 24h following GA-TAVR using TEE is safe for selected patients using our proposed validated predictors.